Respostas

2013-11-21T21:41:11-02:00
S = -( - 4 ) / 1 = 4
P = -5 / 1  = -5


x' = 5 = 5 - 1 = 4
x'' = 5 * -1 = -5

S = { -1, 5}


2013-11-21T21:43:39-02:00
X² - 4x - 5 = 0
a = 1                    b = - 4                          c = - 5
/\ = b² - 4ac
/\ = (- 4)²  - 4 * 1 * (- 5) 
/\ = 16 + 20
/\ = 36
x = - (- 4) + V¨¨¨¨36
      ------------------
            2 * 1
x = 4 + 6
     ---------
         2
x' = 4 + 6 
         2
x' = 10 : 2
x' = 5

x" = 4 - 6 
         2
x" = - 2 : 2
x" = - 1
Resposta: {5, - 1}